Financial management practices for SMEs: cases among SMEs in Kelantan / Nik Ahmad Danial Nik Mohamad Fahmi - Nik Mohamad Fahmi, Nik Ahmad Danial (2012)
Recently, Small Medium Enterprises (SMEs) can be considered as a backbone of the economy. Although their role in the economy is substantial, many SMEs are facing the problem relating to management process. Given that financial management in management process is one of the key aspects the company growth, it is important that this topic is explored in depth. Thus the main purpose of the present study was to investigate the financial management components practiced by the SMEs in Malaysia. The study focused on two main analyses. First, the analysis in six financial management components were identified by previous literature which consist of financial planning and control, financial accounting, financial analysis, management accounting, capital budgeting, and working capital management. For the second analysis is on various types of financial management techniques that were identified under each component stated earlier. The research is conducted on a case study manner which is to concentrate more and consider a situation that is similar to the previous research done. The considered situation is among SMEs in Kelantan area. Source of data are gathered from primary and from secondary data. The primary data is collected and gathered through an interview technique. The findings from the primary data are then is used with secondary data which is taken from previous literature. The findings of this study show six components of financial management practiced by SMEs. There are financial planning and control management, financial accounting management, financial analysis management, management accounting, capital budgeting management and working capital management. A model of financial management practices for SMEs was designed at the end of this study by referring the analysis of findings of this research